2008
DOI: 10.1002/chir.20602
|View full text |Cite
|
Sign up to set email alerts
|

Chiral sign selection on the J‐aggregates of diprotonated tetrakis‐(4‐sulfonatophenyl)porphyrin by traces of unidentified chiral contaminants present in the ultra‐pure water used as solvent

Abstract: Traces of biological contaminants that cannot be detected, but are expected to be present, in ultra-pure water suffice to select the emerging chiral sign in the spontaneous mirror symmetry breaking that takes place during the formation of the J-aggregates of the amphiphilic diprotonated tetrakis-(4-sulfonatophenyl)porphyrin (H(4)TPPS(4)(2-)). This is demonstrated by competition experiments with a chiral cationic surfactant. The sensitivity of the detection depends on the hierarchical control of the H(4)TPPS(4)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
67
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 30 publications
5
67
0
Order By: Relevance
“…Due to the exceptionally strong interaction between the monomers transition dipole moments [16,17] cyanine dyes can form so-called J-aggregates in aqueous solution, which are characterized by a high degree of positional molecular order, a dramatic red-shift and a narrowing of their lowest energetic electronic transition (relative to the dye monomer) [18,19]. Under certain conditions even optically active J-aggregates can be obtained [20][21][22][23][24][25]. The established approach uses the structural information encoded within a chiral template on which the dye molecules spontaneously aggregate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the exceptionally strong interaction between the monomers transition dipole moments [16,17] cyanine dyes can form so-called J-aggregates in aqueous solution, which are characterized by a high degree of positional molecular order, a dramatic red-shift and a narrowing of their lowest energetic electronic transition (relative to the dye monomer) [18,19]. Under certain conditions even optically active J-aggregates can be obtained [20][21][22][23][24][25]. The established approach uses the structural information encoded within a chiral template on which the dye molecules spontaneously aggregate.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile it became also clear, that certain achiral cyanine dyes [23,24] could spontaneously assemble into optically active cylindrical aggregates without any added chiral auxiliaries. The reason for that phenomenon remained unexplained, but just recently it was suggested that biological contaminants present in the ultra-pure water commonly used for preparation could be a source of those effects [25].…”
Section: Introductionmentioning
confidence: 99%
“…13,14 One proposal is that this symmetry breaking is due to the adventitious presence of traces of chiral impurities, 15,16 i.e. , it is once again due to an external driving force.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19] The Direct Synthesis of N-Methyl-tetrakis(4′-sulfophenyl)azacarbaporphyrin J-Aggregates is a self-assembly monomer, and J-aggregates formation is a result of intermolecular substitution of water molecules for sulfonate groups. The unique characteristic of these structures is a strong red shift of absorption bands in UV-Vis spectra of J-aggregates as compared with monomers, caused by resonance absorption.…”
Section: +mentioning
confidence: 99%